2003
DOI: 10.1146/annurev.psych.54.101601.145056
|View full text |Cite
|
Sign up to set email alerts
|

Personality, Culture, and Subjective Well-Being: Emotional and Cognitive Evaluations of Life

Abstract: Subjective well-being (SWB), people's emotional and cognitive evaluations of their lives, includes what lay people call happiness, peace, fulfillment, and life satisfaction. Personality dispositions such as extraversion, neuroticism, and self-esteem can markedly influence levels of SWB. Although personality can explain a significant amount of the variability in SWB, life circumstances also influence long-term levels. Cultural variables explain differences in mean levels of SWB and appear to be due to objective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

54
1,551
5
238

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 2,561 publications
(1,848 citation statements)
references
References 117 publications
54
1,551
5
238
Order By: Relevance
“…There is considerable evidence for an association between personality traits and QoL and subjective well-being [22][23][24]. Personality traits have relatively high stability over the lifecourse, providing a consistent and stable indication of how an individual might perceive and respond to life's challenges [5,25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is considerable evidence for an association between personality traits and QoL and subjective well-being [22][23][24]. Personality traits have relatively high stability over the lifecourse, providing a consistent and stable indication of how an individual might perceive and respond to life's challenges [5,25].…”
Section: Introductionmentioning
confidence: 99%
“…Personality traits have relatively high stability over the lifecourse, providing a consistent and stable indication of how an individual might perceive and respond to life's challenges [5,25]. Some studies have found that self-reported quality of life is associated with aspects of personality such as self-efficacy, optimism, goal adjustment and harm avoidance [5,20,24,26]. Many personality theorists argue for the presence of five superordinate factors which are viewed as being fundamental to the description of personality differences: Extraversion, Neuroticism/Emotional Stability, Agreeableness, Conscientiousness, and Openness to experience (also called Intellect/Imagination).…”
Section: Introductionmentioning
confidence: 99%
“…Barresi et al 1983Barresi et al -1984Lamb 1996;Veenhoven 1996;Ferna´ndez-Ballesteros et al 2001;Diener et al 2003;Oswald et al 2003). This was also the case for the German rural elders.…”
Section: Discussionmentioning
confidence: 88%
“…In our prediction model, we included socio-demographic, health-related, social, environmental, mobility and leisure-related predictor variables from those described above which had proven to contribute substantially to older people's well-being in past studies (e.g. Barresi et al 1983Barresi et al -1984Baldassare et al 1984;Golant 1986Golant , 2004Farquhar 1995;Lamb 1996;Veenhoven 1996;Wenger 1997;Smith et al 1999;Cvitkovich and Wister 2001;Ferna´ndez-Ballesteros et al 2001;Evans et al 2002;Diener et al 2003;Oswald et al 2003) as well as in our previous research (e.g. Mollenkopf et al 2002Mollenkopf et al , 2004.…”
Section: Mobility and Activity Aspectsmentioning
confidence: 99%
See 1 more Smart Citation